Isolasi dan Karakterisasi Fitase dari Mikroba yang Terdapat pada Pupuk Kompos, Rumen Sapi, Ragi dan Tanah Sawah - Prof. Dr.rer.nat. Sajidan (Universitas Sebelas Maret (UNS), 2009)
This research was aimed to isolate and characterize phytase from different sources of higger phosphat complex compounds (compost, cattle rumen, and yeast). Bacteria of phytase was isolated on Luria Bertani (LB) medium and it was incubated on 37 oC for 16 hours. Microbe from yeast was isolated on Pottato Dextrose Agar (PDA) medium. Crude enzyme from supernatant was extracted with centrifuge on 5.000 rpm for 5 minutes. Crude enzyme was characterized for optimum pH, temperature, and influence of matalo ion efector on relative activity of enzyme. B1 isolate from P88 compost had optimum relative activity on pH 5, temperature 50 oC and activator Zn2+ (10-3 and 10-4 M). B2 Isolate from cattle rumen had optimum relative activity on pH 5, temperature 50 oC and activator Zn2+ (10-3 M) and Mg2+ (10-4 M). B3 isolated from soy sauce yeast had optimum relative activity on pH 5, temperature 60 oC, and activators Mg2+ (10-3 M) and, Fe2+ (10-4 M). B4 isolated from tempeh yeast had optimum relative activity on pH 5, temperature 50 oC and activators Mg2+ (10-3 M) and Ca2+ (10-4 M). Key words: phytase, optimum pH, optimum temperature, metalo ion efector, isolate.